2021
DOI: 10.3126/njh.v18i1.36786
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Quality of Life after Valve Surgery in Patients with Rheumatic Heart Disease.

Abstract: Background and Aims: Improvement in quality of life is one of the principal goals of valve surgery. The purpose of this study was to assess the quality of life in patients living with mechanical heart valves. Methods: We conducted a cross-sectional descriptive study among 131 (42 Males, and 89 Female) patients, who had undergone valve procedures at different times in clinic visit of department of cardiac surgery, unit I of Shahid Gangalal National Heart Centre from August 1 till August 29, 2019. Quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 6 publications
3
3
0
Order By: Relevance
“…Our findings are similar to those reported in other studies, showing that age does not effect HRQoL after cardiac surgery [ 39 , 47 ]. A study in Nepal concluded that the amount of HRQoL improvement gained by the elderly after heart valve surgery is similar to that of the young [ 39 ]. Similarly, Sedrakyan et al [ 47 ] found that among patients who have undergone heart valve surgery, age does not limit the HRQoL advantages of surgery.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings are similar to those reported in other studies, showing that age does not effect HRQoL after cardiac surgery [ 39 , 47 ]. A study in Nepal concluded that the amount of HRQoL improvement gained by the elderly after heart valve surgery is similar to that of the young [ 39 ]. Similarly, Sedrakyan et al [ 47 ] found that among patients who have undergone heart valve surgery, age does not limit the HRQoL advantages of surgery.…”
Section: Discussionsupporting
confidence: 93%
“…There was a statistically significant improvement in the mean (±SD) MacNew global scores from 3.47 ± 0.59, 4.88 ± 0.71 and 6.14 ± 0.50 preoperatively, at 3 months and 6 months respectively. Our findings are in keeping with those reported in a study done in Nepal, South Asia which showed improvement in all domains of quality of life after valve replacement for RHD [ 39 ]. Similarly, in another study done in Fiji, an improvement was observed in all HRQoL domains except for mental health.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations